COLLABORATIVE CONSULTING IN HIGHER EDUCATION, FOCUSING ON A STUDENT WITH AUTISTIC SPECTRUM DISORDER - Ferreira Donati, Grace Cristina [UNESP]; Messias Fialho Capellini, Vera Lucia [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
The area of special education has transverse nature; thus, it extrapolates the student as the only target. Its actions should include the teacher as recipient of specific training, which must be continuing, flexible and fully developed in the daily practice of the classroom. The present case report aims to describe collaborative consulting procedures performed by a professional expert in partnership with University managers, with the Faculty of Mathematics members, and focuses on a student with Autistic Spectrum Disorder. Adjustments were applied in the evaluation strategies, including linguistic adequacy and the acceptance of oral responses with the support of resolutions on paper or on the blackboard. The evaluation process was registered through notes, photographs, as well as audio and video recordings. In the end, bearing in mind the failure in previous opportunities, the teachers reported the use of the strategies to assess the student learning as decisive.
Keywords: Collaborative consulting; Autism spectrum disorder; Higher education